Pelatihan Perawatan Alat Produksi pada Usaha Mikro Keripik Singkong di Desa Sumberjati Kabupaten Mojokerto - Rijanto, Achmad; Rahayuningsih, Suesthi (ABDIMAS NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Maintenance of production equipment was one of the production activities in the micro cassava chip business in Sumberjati village, Mojokerto district. With the age of the production equipment, it could save production costs. Therefore it was necessary to have an understanding to treat production equipment regularly. The purpose of this community service activity was to provide an understanding of cassava chip micro entrepreneurs about the importance of periodic maintenance of cassava chip cutting machine tools, as an effort to increase production output. The method of implementing this service was the training method. The results achieved from this activity were an increase in understanding of partners about the maintenance of cassava chip cutting machine production equipment by 60% for theory and 75% for practice.